We begin by using the following log rule to simplify our question:

log

ab= loga+ logb

We can write our question as:

y= log_{2}6x= log_{2}6 + log_{2}x

The first term, log_{2}6, is a constant, so its derivative is 0.

The derivative of the second term is as follows, using our formula:

`(dy)/(dx)=(log_2e) (1/x)=(log_2e)/x`

The term on the top, log_{2}*e*, is a constant. If we need a decimal value, we can work it out using change of base as follows:

`log_2e=(log_10e)/(log_10 2)=1.442695041`

Easy to understand math videos:

MathTutorDVD.com